Figure 2 from: Stur E, Borkent A (2014) When DNA barcoding and morphology mesh: Ceratopogonidae diversity in Finnmark, Norway. ZooKeys 463: 95-131. https://doi.org/10.3897/zookeys.463.7964 - Stur, Elisabeth; Borkent, Art (Zenodo, 2014)
Figure 2 - Taxon-ID tree of the studied Ceratopogonidae specimens based on the neighbor joining algorithm from aligned COI sequences using partial deletion for areas with gaps and 1000 bootstrap replicates in MEGA 5.2. All included sequences were longer than 500 bp. Bootstrap values shown on branches supported by more than 90% of the bootstrap replicates.